THE SUPERIORITY OF THE WHITES IN LEOROI JONES’THE DUCTMAN - Pioro Benevolent Lariesto (Muse: Jurnal of Art, 2023)
This journal will primarily discuss about ambivalence and undecidability within a binary opposition which can be found in LeRoy Jones’ work titled The Dutchman. This study is based upon Derrida’s deconstructive theory, with the intention to perform a critical analysis towards said drama using an extrinsic approach. The problem in this study will be answered using qualitative approach. The result of the research towards the binary opposition shows that each binary opposition possesses ambivalence. This ambivalence then becomes a trait of undecidability in the text. The conclusion of this study is that the texts do shows undecidability and shows the “white skin superiority” ideology.